Preoperative Assessment of Cervical Involvement in Endometrial Cancer by Transvaginal Ultrasound and Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Alcazar, Juan Luis; Carazo, Patricia; Pegenaute, Leyre; Gurrea, Elena; Campos, Irene; Neri, Manuela; Pascual, Maria Angela; Guerriero, Stefano (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Objective To compare the diagnostic accuracy of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) for detecting cervical infiltration by endometrial carcinoma using meta-analysis assessment.Methods An extensive search of papers comparing TVS and MRI for assessing cervical infiltration in endometrial cancer in the same set of patients was performed in Medline (Pubmed), Web of Science, and the Cochrane Database. Quality was assessed using QUADAS-2 tool (Quality Assessment of Diagnostic Accuracy Studies-2). Quantitative meta-analysis was performed.Results Our extended search identified 12 articles that used both techniques in the same set of patients and were included in the meta-analysis. The risk of bias for most studies was high for patient selection and index tests in QUADAS-2. Overall, the pooled estimated sensitivity and specificity for diagnosing cervical infiltration in women with endometrial cancer were identical for both techniques [69 % (95 % CI, 51 %–82 %) and 93 % (95 % CI, 90 %–95 %) for TVS, and 69 % (95 % CI, 57 %–79 %) and 91 % (95 % CI, 90 %–95 %) for MRI, respectively]. No statistical differences were found when comparing both methods. Heterogeneity was high for sensitivity and moderate for specificity when analyzing TVS and moderate for both sensitivity and specificity in the case of MRI.Conclusion TVS and MRI showed very similar diagnostic performance for diagnosing cervical involvement in women with endometrial cancer.
Keywords: endometrial cancer; ultrasound; MRI; cervical infiltration; gynecology